PENGARUH PENYAJIAN LAPORAN KEUANGAN DAERAH DAN AKSESIBILITAS LAPORAN KEUANGAN DAERAH TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH ( Studi Pada SKPD Pemerintah Kabupaten Rokan Hilir) - -, Sumiyati; -, Zulbahridar; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the influence of regional financial statement and financial statement accessibility on financial management accountability. The populations in this study were officials echelon II dan III which consist of heads of SKPD, SKPD finance department expenditures and receipts SKPD in district Rokan Hilir. The sampling method using purposive sampling method. The data of this research using primary data directly through questionnaire and analyzed using SPSS versionÂ 16. The data were analyzed to test the hypothesis using multiple linear regression analysis approach. The results of this study showed regional financial statement and accesibility of financial management accountability effect on financial management.Keywords: regional financial statement, accessibility, and accountability